Replication Study of "Coase and cap-and-trade" (Zaklan 2023) - Adrien Coiffard; Rose Deperrois; Alexandre Sauquet; Julie Subervie (Institute for Replication (I4R), 2024)
Zaklan (2023) examines the coasean independence property in the EUETS. To test this property, the author studies whether emissions are independent from the free allowance allocation. Some allowances were given for free to all EU Member States until 2012. From 2013 allowances were fully auctioned, apart in 10 countries that were granted an exception to continue to give free allowances to their firms. Treated firms are firms located in countries that do not receive free allowances anymore. Control firms are firms located in countries that continue to receive free allowances. The main analysis is led at the firm level using annual data from 2009 to 2017. Two way fixed effects estimators are combined with 1 to 1 matching to estimate the impact of the treatment on firms' emissions. The main claim is that the independence property holds overall and on large emitters. Moreover, there is suggestive evidence that the independence property does not hold for small emitters. The study is reproducible. The STATA code runs smoothly and enough information is available to reproduce the main results using the R software. We apply different robustness checks on: the matching strategy, the specification, the level of clustering, the definition of the treatment and the definition of the cutoff that differentiates small and large emitters. We generally align with the author's assertion that the independence property is not rejected both overall and for large emitters. However, in most instances, we do not confirm the suggestive evidence that the independence property is rejected for small emitters. Moreover, the change in the definition of the treated firms is a robustness check to be considered separately as it leads to sign reversal in most regressions.
Keywords: 330